Peran Kepala Sekolah Dalam Membangun Pendidikan Unggul Melalui Inovasi Kepemimpinan Berbasis Teknologi - Harly, Muhammad Riadhi; Rinaldi, Rinaldi; Hasri, Salfen; Sohiron, Sohiron (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
Leadership innovation enables excellent educational innovation and produces professional teachers and educational talent. This allows for first-class, effective and efficient training. The researchers will describe the role of 044 Tapun elementary school principals in creating quality education through technology-based leadership innovation. Fieldwork is part of this research and is conducted as a type of qualitative research. Observation, documentation, and interviews are used to collect data. This data analysis uses deductive data analysis. This means that the theory is based on field data. This study uses a descriptive qualitative research approach. This means collecting data in natural environments in order to interpret phenomena that occur. Additionally, a case study approach is used to answer questions about how or why phenomena are studied. Karya Indah, Director of SDN 044, explores and implements creative and innovative ideas to solve problems facing schools. Formation of a school committee to deal with technology and develop school facilities and infrastructure such as: B.Improve and effectively utilize long-distance internet networks and collaborate with specific stakeholders to achieve better education.